The role of anxiety in the association between nutrition literacy and health-related quality of life among college students - Siwei Liu; Zeyu Meng; Shuxian Wang; Hehe Wang; Dan Fan; Mengqing Wu; Zhenglong Jiang; Qing Chen; Quanan Wang; Zhe Liu; Jun Liu; Yan Xie (Scientific Reports, 2024)
Abstract The health-related quality of life (HRQOL) of college students is not promising and needs to be improved through effective interventions. This study aimed to investigate the associations of nutrition literacy (NL) with HRQOL and anxiety among college students, and to identify the role of anxiety in the relationship between NL and HRQOL. The cross-sectional survey was conducted via the “Wenjuanxing” platform from September to November 2023. The Food and Nutrition Literacy Questionnaire (FNLQ), the Generalized Anxiety Disorder (GAD-7) diagnostic tool and the SF-12 scale were used to assess NL, anxiety, and HRQOL, respectively. Logistic regression models, mediation analysis, additive and multiplicative interaction analyses were used. 2066 college students participated in the analysis. After adjusting for potential confounders, we found that college students with higher NL had higher HRQOL (OR = 2.52, 95% CI: 2.09–3.03, p < 0.001) and a lower risk of anxiety (OR = 0.53, 95% CI: 0.39–0.73, p < 0.001). Additionally, anxious college students had lower HRQOL (OR = 0.16, 95% CI: 0.11–0.24, p < 0.001). Furthermore, mediation analysis confirmed that anxiety was a partial mediator of the relationship between NL and HRQOL (β = 0.600, 95% CI: 0.406–0.779/0.430–0.818). Significant additive interactions were found between NL and Anxiety (RERI = 6.96, 95% CI: 2.74–11.17; AP = 0.51, 95% CI: 0.37–0.64; SI = 2.21, 95% CI: 1.58–3.07). Higher levels of NL are associated with better HRQOL and lower anxiety among college students. Additionally, anxiety partially mediated the relationship between NL and HRQOL. Furthermore, there is a synergy between NL and anxiety.